KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMA DALAM MENYELESAIKAN SOAL MATRIKS - Anggun Pratiwi; Alpha Galih Adirakasiwi (IKIP Siliwangi, 2022)
Mathematical problem solving ability is an ability that every student must have, students must be able to find solutions to solve problems and choose strategies to solve problems. Indicators of mathematical problem solving include being able to understand the problem, being able to transform the information obtained on the problem, being able to perform problem solving skills or strategies, and being able to conclude the answers or results obtained. The purpose of this research is to measure the level of students' mathematical problem solving ability in solving matrix problems. The method used in this study is a descriptive method with a qualitative approach. The subjects in this study were students of class XI IPS in one of the senior high schools in Karawang Regency. From the total class there were 12 students who were the subjects of the study. Collecting data using three questions about the description of the matrix material and observations, each question refers to an indicator. The results of this study indicate that students in solving matrix problems still have difficulties in achieving indicators of problem solving abilities including indicators of understanding, skills and inferences. Based on the results of research that has been done there are still students who are not able to solve the problems given, students' mathematical problem solving abilities are still in the low category, it is hoped that students will continue to learn so that they are able to solve mathematical problems.